pengembangan program pelatihan fisik bayangan rancang gerak bulutangkis dan pengurangan masa istirahat untuk peningkatan power, kecepatan reaksi dan recovery - Himawan Wismanadi, (Kepelatihan Olahraga, 2011)
Developing Physical Training Program for Shadow Motion Design in Badminton and Rest Time Reduction to Increase Power, Speed Reaction and Recovery, Sport Science Study Program of Post Graduate Program, State University of Surabaya. The Supervisor in this Dissertation is  Profesor . Dr. H. Hari Setijono, M.Pd and C0- Supervisors: Profesor Dr. drg. Soetanto Hartono, M.Sc, Consultants (1). Profesor Dr. H. Sunarto, M.Sc. dan (2). Profesor I Ketut Budayasa, Ph.D